Allégeance et sujétion dans les territoires frontaliers entre Royaume de France et Duché de Luxembourg au 16e siècle. Une histoire «par le bas» de la construction d’une frontière de souveraineté - Gérardin, Emmanuel (Hémecht. Zeitschrift für Luxemburger Geschichte = Revue d’histoire luxembourgeoise, 2025)
Abstract: „During the 16th century, a border of sovereignty was gradually being devised between the Kingdom of France and the Duchy of Luxembourg. At the dawn of modern times, a border was not thought of as a fixed and delimited line but as a moving space, characterized by the entanglement of feudal rights, shaped by the relations between various seigniorial entities. This article reflects on the transformation of feudal structures inherited from the Middle Ages, marked by subjection to local lords, and the gradual emergence of a new conception of sovereignty, territorializing power and asserting state authority over larger spaces. The Duchy of Lorraine and Bar was a buffer state caught up in the confrontation between the Valois and the Habsburgs. It became part of a border march between the Meuse and the Moselle marked out by fortresses: a clear expression of the military front produced by the new balance of power. However, the dynamics of war alone cannot account for the efforts made to stabilize the border. The border was also a space of negotiation around which a princely order emerged. The recognition of a judicial and political concept of sovereignty implied a new relationship between princely power and society, shaped by a new administrative system of controlling a territory and its population. The border came to be redefined as the outward face of a society organized around the sovereignty of the state. Yet this process was far from being achieved at the beginning of the 17th century.“
Keywords: Herzogtum Bar; Lothringen

Vereinendes und Trennendes. Grenzen und ihre Wahrnehmung in Lothringen und preußischer Rheinprovinz 1815–1914 - Schlesier, Stephanie (Die Grenze als Raum, Erfahrung und Konstruktion, Deutschland, Frankreich und Polen vom 17. bis zum 20. Jahrhundert, 2007)
Keywords: Lothringen; Staatsgrenze

Von sichtbaren und unsichtbaren Grenzen. Die Annexion von 1871 und ihre Auswirkungen auf das annektierte Lothringen bis zum Ersten Weltkrieg - Schlesier, Stephanie (Grenzregionen. Ein europäischer Vergleich vom 18. bis zum 20. Jahrhundert, 2007)
Keywords: Annexion; Lothringen; Staatsgrenze